SEL FOTOVOLTAIK CAIR PASANGAN ELEKTRODA CuO/CERMIN DALAM LARUTAN ELEKTROLIT NaCl - Novi Rahmawanti; Novrian Dony (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2017)
The purpose of this study are to get  liquid photovoltaic cell made using a simple material and test their capability. The photovoltaic cell is made by using a CuO / Mirror electrode pair then electric current that resulted was tested under sunlight in a NaCl solution. From the electric current data can be concluded that CuO / mirror pair electrodes can be used in liquid photovoltaic cells, but the CuO / mirror pair is less stable. This CuO / mirror electrode pair provides the greatest current of 1.664 mA.Keywords: Phothovoltaic cells, pair electrode,  Current